2007
DOI: 10.1073/pnas.0708739104
|View full text |Cite
|
Sign up to set email alerts
|

Duplication and segregation of the actin (MreB) cytoskeleton during the prokaryotic cell cycle

Abstract: The bacterial actin homolog MreB exists as a single-copy helical cytoskeletal structure that extends between the two poles of rod-shaped bacteria. In this study, we show that equipartition of the MreB cytoskeleton into daughter cells is accomplished by division and segregation of the helical MreB array into two equivalent structures located in opposite halves of the predivisional cell. This process ensures that each daughter cell inherits one copy of the MreB cytoskeleton. The process is triggered by the membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
111
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(132 citation statements)
references
References 35 publications
16
111
2
Order By: Relevance
“…3G). This pattern was reminiscent of many helical patterns present in bacterial cells (20,(22)(23)(24)(25)(26)(27)(28). Note, however, that these RNArelated patterns were more diffuse than most helical patterns revealed by protein labeling.…”
Section: Estimation Of Number Of Egfp Molecules Per Cell After Rna Inmentioning
confidence: 84%
“…3G). This pattern was reminiscent of many helical patterns present in bacterial cells (20,(22)(23)(24)(25)(26)(27)(28). Note, however, that these RNArelated patterns were more diffuse than most helical patterns revealed by protein labeling.…”
Section: Estimation Of Number Of Egfp Molecules Per Cell After Rna Inmentioning
confidence: 84%
“…The FtsZ-MreB colocalization persists for most of division until the late predivisional cell stage, when MreB readopts a patchy/ helical distribution (6,19). Such cell-cycle dynamics in MreB localization is not unusual, although the timing of ring localization appears to vary considerably among bacteria (21,22).…”
mentioning
confidence: 94%
“…This view has been challenged, however, by more recent results. At least in the original images of E. coli (20,25), extended MreB helices were shown to be artifacts of the fluorescent protein tag (26,27). Later fluorescence studies reported that, instead of extended helices, MreB localizes in tight patches that, driven by PG synthesis, move circumferentially around the cell (28)(29)(30).…”
mentioning
confidence: 99%